PERJANJIAN INTERNASIONAL TENTANG KESEPAKATAN MASYARAKAT EKONOMI ASEAN DAN TIONGKOK DALAM HUKUM NASIONAL INDONESIA - Elvardi, Jean (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
Indonesiaâs participation in international treaties can not be avoided in global situation, but it does not mean to exclude the national interest especially with regard the protection of Indonesian workers. The government must necessarily put the national interest as the main objective, and if the country is in unfavorable conditions even harming national interests, it should be evaluated or if necessary aborted.